Тechnique for growth of CSI:TL crystals with internal radioisotope for nuclear physics - Shpilinskaya, A.L.; Kudin, A.M.; Kolesnikov, А.V.; Didenko, A.V.; Kudin, K.A. (Вопросы атомной науки и техники, 2018)
CsI:Tl crystals have been grown by Stockbarger technique in sealed quartz ampoules. Grown ingots do not adhere to the material of the container. Ready crystals have no residual stresses and do not break during subsequent
mechanic treatment. Vibration absorption of grown crystals contains no bands of
OH⁻
or
CO²⁻₃
ions in the IR region. After irradiation the electronic absorption has no bands of F- or FA-color centers in the visible region. Spectrometric characteristics of the grown crystals are not inferior to standard. Developed technique is recommended for
growth of CsI:Tl scintillation material with internal source of radiation. The peculiarity of the method is the dehydration of raw material at T ⩽ 40°C under conditions which exclude photolysis of salt. Методом Стокбаргера в герметичних кварцових ампулах вирощено кристали CsI:Tl, які не прилипають
до матеріалу контейнера, не мають залишкових напружень і не руйнуються в процесі подальшої механічної
обробки. Спектри коливального поглинання отриманих кристалів CsI:Tl не мають смуг поглинання в ІЧобласті спектра, що обумовлені іонами
OH⁻
і
CO²⁻₃
, а електронне поглинання у видимій області після опромінення не мають смуг поглинання центрів забарвлення F- и FA-типів. Спектрометричні характеристики вирощених кристалів не поступаються еталону. Метод рекомендовано для вирощування сцинтиляторів з ізотопами, що введені до кристалічної ґратки, і відрізняється дегідратацією сировини при T ⩽ 40°C в умовах,
що виключають фотоліз солі. Методом Стокбаргера в герметичных кварцевых ампулах выращены кристаллы CsI:Tl, которые не прилипают к материалу контейнера, не имеют остаточных напряжений и не разрушаются при последующей
механической обработке. Спектры колебательного поглощения выращенных кристаллов CsI:Tl не содержат
полос поглощения в ИК-области спектра, обусловленных ионами
OH⁻
и
CO²⁻₃
, а электронное поглощение в
видимой области после облучения не имеет полос поглощения центров окраски F- и FA-типов. Спектрометрические характеристики выращенных кристаллов не уступают эталону. Метод рекомендован для выращивания сцинтилляторов с изотопами, введенными в кристаллическую решетку, и отличается дегидратацией
сырья при T ⩽ 40°C в условиях, исключающих фотолиз соли.